2016
DOI: 10.1590/1516-4446-2015-1714
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and sociodemographic characteristics: baseline findings of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Objective: To assess the prevalence of common mental disorders (CMD) and the association of CMD with sociodemographic characteristics in the Brazilian Longitudinal Study of Adult Health (ELSABrasil) cohort. Methods: We analyzed data from the cross-sectional baseline assessment of the ELSA-Brasil, a cohort study of 15,105 civil servants from six Brazilian cities. The Clinical Interview Schedule-Revised (CIS-R) was used to investigate the presence of CMD, with a score X 12 indicating a current CMD (last week). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
3
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 28 publications
7
33
3
21
Order By: Relevance
“…In a cohort study with 15,105 people from six Brazilian cities, the authors identified that the prevalence of CMD was more frequent among women (33.8%), showing a lower rate than in the present study (8) . We found that the prevalence of CMD identified in the present study shows lower results than those presented in most national and international studies conducted in rural and urban areas.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…In a cohort study with 15,105 people from six Brazilian cities, the authors identified that the prevalence of CMD was more frequent among women (33.8%), showing a lower rate than in the present study (8) . We found that the prevalence of CMD identified in the present study shows lower results than those presented in most national and international studies conducted in rural and urban areas.…”
Section: Discussioncontrasting
confidence: 86%
“…In a cohort study with 15,105 people from six Brazilian cities, the authors identified that the prevalence of CMD was more frequent among women (33.8%), showing a lower rate than in the present study (8) .…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations